Atlas of Critical Care Procedures (Springer International Publishing, 2018)
This atlas is designed to provide an all-inclusive resource that describes step by step how to perform the essential bedside procedures required to provide optimal care to the critically ill patient. Detailed descriptions of these procedures, with sequential photographs depicting each critical step, provide an in depth understanding of the anatomy, critical technical steps and common pitfalls to both military and civilian trainees. For the advanced professional operator, this atlas will provide a rapid refresher of the critical steps and is an excellent teaching resource, based on the decades of collective experience accumulated by the authors. The top quality photographs of perfused and ventilated cadavers makes this atlas a standard reference for surgeons, critical care physicians, nurses and all critical care professionals. .